Prīdī bannānusō̜n 2561 - Kasidit ʻAnanthanāthō̜n (Krung Thēp : Samnakphim Sayām Parithat, 2018)
Biography of Pridi Banomyong and educational change in Thailand.
"Mahāwitthayālai Thammasāt rūam kap Samnakphim Sayām Parithat čhat phim pen thīralưk nư̄ang nai wan Prīdī Phanomyong 11 Phrưtsaphākhom 2561."
Includes bibliographical references.
In Thai, with one article in English.
Keywords: Pridi Banomyong; Statesmen -- Thailand -- Biography; Prime ministers -- Thailand -- Biography